Prevalence of attention deficit hyperactivity disorder in relation to the sex of school children - Fernando Luiz Cardoso; Samantha Sabbag; Thais Silva Beltrame (Universidade Federal de Santa Catarina, 2007)
The main objective of this research was to verify possible gender-based differences in the subtypes of ADHD. It was a descriptive-exploratory and non-probabilistic study. Eighty-four children aged between 6 and 16years were indicated for participation by their teachers, and the DSM-IV and EDAH scale assessments were then applied. Seventy-one participants were identifi ed as positive by at least one of these scales, as a result of which 51 boys and 20 girls were enrolled on the study, at an average of 3.5 boys for each girl. This study upholds the results of the literature review in terms of ADHD prevalence among boys. This difference is probably the result of the prevalence among girls being underestimated due tomore inattention symptoms than hyperactivity behavior. RESUMO Esta pesquisa tem como objetivo verifi car possíveis diferenças de sexo nos subtipos do TDAH. Está caracterizada como descritiva-exploratória, não probabilística. Foram indicadas pelos professores 84 crianças, com idade entre 6 e 16 anos, nas quais foram aplicadas as escalas de avaliação DSM-IV e EDAH. Destas, 71 obtiveram indicativos positivos do transtorno através de pelo menos um dos instrumentos, sendo 51 meninos e 20 meninas, ou seja, na média de 3,5 meninos para cada menina. A amostra obteve um resultado dentro do esperado quanto à prevalência do TDAH no sexo masculino. Diferença que talvez ocorra porque as meninas são subdiagnosticadas por possuírem mais sintomas de desatenção que hiperatividade.